Peningkatan Kecepatan Pengeluaran Kolostrum Dengan Perawatan Totok Payudara Dan Pijat Oksitosin Pada Ibu Post Partum - Kuswati Kuswati; Henik Istikhomah (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Totok Payudara, Oxytocin Massage And Colostrum. The purpose of this study was to determine differences in time of leaking colostrums in mothers post partum in doing oxytocin massage with totok payudara. This study design used is quasiexperimental design with the design Nonequivalent Control Group Design. Reserch conducted at the midwives (BPM) at health centers working area Klaten who were divided into 2 groups, i.e an experimental group consisting of 30 respondens to whom oxytocin massage was given and a control group consisting of 30 responden to whom totok payudara was given. Bivariate data analysis using statistical test used is t –test. Results of the study showed the average time of leaking colostrums in experimental and control groups were 152,67 minutes and 137,23 minutes. The result of hypothesis test using T-test obtained the value of p= 0.668 (p>0.05). Conclusion: there is no difference time between oxytocin massage and totok payudara to the leaking colostrum